Hydrogen evolution on a pseudomorphic Cu-layer on Ni(111) - a theoretical study - Santos, Elizabeth del Carmen (2010)
Hydrogen evolution on a monolayer of copper on Ni(1 1 1) has been investigated by a combination of density functional theory and a model developed in our own group. The lattice constant of nickel is only about 2.5% shorter than that of copper; therefore the nickel substrate has only a minor effect on the surface d band of the adsorbed copper. However, there is a strong chemical effect which enhances the interaction of hydrogen with the Cu/Ni(1 1 1) surface as compared to Cu(1 1 1). Consequently, the adlayer promises to be a cheap catalyst that is significantly better than pure copper.